FREE CASH FLOW, AUDIT QUALITY, AND EARNINGS MANAGEMENT: MODERATING EFFECT OF AUDIT COMMITTEE EXPERTISE - Diana Awaliyah; Mohamad Zulman Hakim (ZILLZELL MEDIA PRIMA, 2026)
The purpose of this study was to determine the effect of Free Cash Flow, Audit Opinion, and Audit Quality on Earnings Management, with Audit Committee Expertise as a Moderating Variable, in the food and beverage sector listed on the Indonesia Stock Exchange for the 2020-2024 period. The data analysis method used was panel data regression analysis using the data processing program eViews 12. The research sample consisted of 31 companies. Sampling was conducted using a purposive sampling technique. The results showed that: 1) Free cash flow has a negative effect on earnings management; 2) Audit opinion has no effect on earnings management; 3) Audit quality has no effect on earnings management; 4) Audit committee expertise strengthens the effect of free cash flow on earnings management; 5) Audit committee expertise weakens the effect of audit opinion; 6) Audit committee expertise weakens the effect of audit quality on earnings management.